Do Clients’ Enterprise Systems Affect Audit Quality and Efficiency? - Pincus, Morton; Tian, Feng; Wellmeyer, Patricia; Xu, Sean Xin (Contemporary Accounting Research, 2017)
Abstract Enterprise systems ( ES s) are widely used to support business processes along the enterprise value chain. It has been shown that ES s, by integrating business functions and making information about day‐to‐day activities available, enhance operational transparency and improve the internal information environment. However, while ES ‐based business infrastructures can offer many benefits, their prevalence and increased complexity have also brought new challenges to external auditors. Motivated by the prominence of this issue for auditors and regulators and by the scarcity of research jointly examining ES s and auditors’ work, we investigate whether the presence and extent of client firms’ ES implementations are related to the quality and efficiency of auditors’ work. Using proprietary archival data on ES implementations and controlling for self‐selection, we find that ES implementation improves the quality and efficiency of current and future years’ audit work. Specifically, there are fewer restatements, a greater likelihood of auditors issuing going‐concern opinions to firms that do not survive, higher accruals‐based auditing quality, a lower likelihood of Form 10‐K filing delays, and generally lower audit fees. We further show that the benefits of ES s generally increase with the scope of implementation and are generally greater when the ES includes accounting and finance systems. Inconsistent with improvement in the quality of auditors’ work, we find no evidence that ES s help auditors identify material weaknesses in advance of restatement announcements and we find that, even in the presence of ES s, auditors issue an excessive number of going‐concern opinions to clients that survive.